Design as a tool in the Module History of Architecture. Learning by Doing - Cimadomo, Guido (My University, 2017)
We present the teaching experience of the History of Architecture II module related to the last three academic years when we have experienced the introduction of a practical exercise aimed at actively learning the theoretical content of the subject: the history of architecture between the fifteenth and eighteenth centuries. The problem-based and the learning-by-doing methodologies have been applied within the framework of a broader educational innovation project that has involved different undergraduate subjects in architecture. The exercise is based on the realization of a project at the level of a preliminary project of a building contextualized in the Renaissance or the Baroque eras, varying this last parameter each year. Each student had to identify himself in the role of an architect of the modern era, search for a patron and choose the typology to build among those studied in the theoretical classes. The freedom offered in all these parameters has allowed each student to freely search for their hobbies and personal interests, being an incentive to carry out the task assigned. This exercise requires a different approach to the buildings studied throughout the semester, to understand the logic and compositional rules underlying each typology, uses, needs, as well as constructive solutions. The preliminary phase of the exercise also requires a historical understanding of the patron and his hobbies, of the geographical environment in which the exercise will be carried out, as well as the cultural and political context of the chosen temporal arc. The aim is to promote learning through project activity even in traditionally theoretical subjects such as the history of architecture, generating dynamics closer to the expectations of students without sacrificing the learning required by the curriculum. The results obtained, both quantitative and qualitative, contrasted by anonymous surveys conducted at the end of each year, show a greater linkage of students to the subject, a deeper learning of the compositional rules of the studied ages, and greater satisfaction with the dynamics applied, without sacrificing the objectives of explaining the processes in the environment of the society of the time and its direct relationship with the present. As with previous experiences, we demonstrate the need to adapt teaching methodologies to the generational changes of the students that study for the degree in architecture to achieve the pedagogical objectives of the training of architects in the 21st century.
Cimadomo, G. (2017), Design as a tool in the module History of Architecture. Learning by Doing. ICERI2017 Proceedings)
Keywords: Arquitectura - Historia - Estudio y enseñanza; PBL; ABP; Historia de la Arquitectura; Aprendizaje activo; Aprender haciendo; Learning by doing; Active learning